Multicultural competencies training programs for health care staff and health students in academic and professional settings, - Oliveira, Aliete Cristina Gomes Dias Pedrosa da Cunha (2021)
Objective: The aim of the proposed scoping review is to identify training programs in multicultural competencies for health care staff and health students in professional and academic settings. Introduction: Cultural competence training for health care professionals is an imperative challenge in today's culturally diverse societies to ensure that all people receive equitable and effective health care, particularly those from culturally diverse backgrounds.